2020
DOI: 10.29052/ijehsr.v8.i4.2020.275-287
|View full text |Cite
|
Sign up to set email alerts
|

The multifactorial burden of Type 2 Diabetes mellitus: a study from clinical settings of University Hospital, Karachi, Pakistan

Abstract: Background: Diabetes is a multifactorial disease posing a socioeconomic threat to the worldwide community. The prevalence of Type 2 Diabetes Mellitus (T2DM) is continuously increasing in Pakistan and becoming a serious concern for the general public as well as concerned clinicians. This case-control study aimed to analyze the modifiable and non-modifiable risk factors associated with T2DM in the Pakistani population. Methodology: A structured questionnaire was filled by the T2DM patients attending the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…High prevalence of peripheral arterial disease in patients with Type 2 diabetes mellitus has been shown in a study conducted in Eastern India, where results showed that 53% of patients had asymptomatic mild PAD and 14% had moderate PAD 15 . Another study conducted in Natal, Brazil, showed peripheral arterial disease in 13.7% of patients who had Diabetes Mellitus 16 . Asymptomatic peripheral arterial disease has been linked with higher cardiovascular mortality and morbidity.…”
Section: International Journal Of Endorsing Health Science Researchmentioning
confidence: 96%
See 1 more Smart Citation
“…High prevalence of peripheral arterial disease in patients with Type 2 diabetes mellitus has been shown in a study conducted in Eastern India, where results showed that 53% of patients had asymptomatic mild PAD and 14% had moderate PAD 15 . Another study conducted in Natal, Brazil, showed peripheral arterial disease in 13.7% of patients who had Diabetes Mellitus 16 . Asymptomatic peripheral arterial disease has been linked with higher cardiovascular mortality and morbidity.…”
Section: International Journal Of Endorsing Health Science Researchmentioning
confidence: 96%
“…Asian ethnicity and late diagnosis of diabetes Mellitus in our setup could be the cause for our findings. Assessment of largevessel PAD prevalence in patients with clinical features of PAD will dramatically underestimate the true large-vessel PAD prevalence 16 . Detection of Peripheral arterial disease at the early subclinical stage can be a double edge sword, as it may be used as a surrogate marker for the prevention of cardiovascular and cerebrovascular diseases and identify patients who need early treatment and intervention, but at the same time may lead to overtreatment and may not prove to be costeffective.…”
Section: International Journal Of Endorsing Health Science Researchmentioning
confidence: 99%
“…Diabetes increases the risk of complications like cardiovascular disease, which is one of the leading causes of death globally. 1,2 A local study reveals that among diabetic patients frequency of generalized anxiety disorder was 14.4% and cardiovascular disease was 12.6% 3 . Different studies showed that the stress ranges from 25.5% to 37.4% among diabetic patients the prevalence of anxiety and depression was higher than stress level.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that by 2025, there will be around 380 million diabetics and 418 million people with impaired glucose tolerance worldwide 2 . Diabetes complications, such as cardiovascular disease, stroke, neuropathy, nephropathy, and retinopathy, result in increased disability, decreased life expectancy, and enormous health costs for almost every society 3 . According to the most recent IDF Atlas 2, in Pakistan, 33 million people live with Type 2 Diabetes Mellitus, making it the third largest diabetes population in the world 4 .…”
Section: Introductionmentioning
confidence: 99%